Training Needs of Vegetable Growers in Jaunpur District of Uttar Pradesh - S.P. Sonkar and O.P. Mishra, (Indian Journal of Extension Education, 2015)
Importance of training as an indispensable instrument for the development of skill and knowledge cannot be ignored.Training has become a critical input especially in view of the growing sophistication in agricultural technology as well asits cost intensive nature. However, no training programme would bring desirable change in knowledge, skill, attitude andother behavioural components of the farmer unless it is need based. Much can be achieved in the direction of increasingvegetable production and productivity if the farmers are trained after assessing their level and extent of training needs andrequirements. To know the profile and the level of training need of farmers to carry out their vegetable farming the studywas undertaken in Karanjakala block of Jaunpur district of Uttar Pradesh. Two hundred fourteen (214) vegetable growerswere randomly selected as respondents for the purpose of study. The findings reveal that the Majority of the respondentswere in 36 to 54 years age group, having education up to Intermediate, from Other Backward Caste Category, from jointfamilies, having large size family, large land holdings, agriculture as main occupation, from medium income group, andhaving 21 to 32 years of farming experience. Respondents' first choice of training was in the area of Pumpkin cultivationfollowed by Bottle Gourd (2nd rank), and Radish (3rd rank). Pumpkin cultivation and Bottle Gourd cultivation were mostpreferred vegetable for training. While, the training need preferences in main areas and sub areas of vegetable cultivationare different for each vegetables.